Candida albicans gene mistranslation as a modulator of host-pathogen interaction and pathogenesis - Lopes, Edgar Silva (2021)
Candida albicans is the major fungal pathogen in humans, causing diseases ranging from mild skin infections to severe systemic infections in immunocompromised individuals. The pathogenic nature of this organism is mostly due to its capacity to proliferate in numerous body sites and to its ability to adapt to drastic changes in the environment, such as pH, oxidative stress, temperature and osmolarity. C.albicans exhibit a unique translational system, decoding the leucine-CUG codon ambiguously as leucine (3%) and serine (97%), using a novel serine tRNA (tRNACAG Ser). That is aminoacylated by Seryl-tRNA synthetase (SerRS) and the LeucyltRNA synthetase (LeuRS). Exposure of C. albicans to macrophages, oxidative and pH stress and antifungals increases Leu misincorporation levels from 3% to 15%, suggesting that C. albicans could regulate mistranslation levels. The aim of this study was to identify molecules and pathways involved in the regulation of this genetic code ambiguity, and ultimately contribute to better understand this unique translational process. To accomplish this, the levels of the SerRS and LeuRS were determined under different physiological conditions, using a GFP sensor where the GFP opening reading frame was fused to the promoters of the SerRS and LeuRS genes (caSES1 and caCDC60 respectively). The data revealed that increased Leu incorporation at CUG codons is associated with higher LeuRS/SerRS ratio. To identify putative regulators (kinases and transcription factors (TF)) of SerRS and LeuRS expression, C. albicans kinase and TF knockout (KO) strains were transformed with the sensor and the expression of both aaRSs was quantified. Our data allowed us to identify the Transcription Factors Rph2 and Hap31 and Cbk1 kinase as putative regulators of the expression of both SerRS and LeuRS.